Towards Treating Multiple Sclerosis Progression - Darius Häusler; Martin S. Weber (MDPI AG, 2024)
Multiple sclerosis (MS) is an inflammatory, demyelinating disease of the central nervous system (CNS). In most patients, the disease starts with an acute onset followed by a remission phase, subsequent relapses and a later transition to steady chronic progression. In a minority of patients, this progressive phase develops from the beginning. MS relapses are characterized predominantly by the de novo formation of an inflammatory CNS lesion and the infiltration of immune cells, whereas the pathological features of MS progression include slowly expanding lesions, global brain atrophy and an inflammatory response predominantly mediated by macrophages/microglia. Importantly, this CNS-intrinsic pathophysiology appears to initiate early during the relapsing-remitting disease phase, while it turns into the key clinical MS feature in later stages. Currently approved disease-modifying treatments for MS are effective in modulating peripheral immunity by dampening immune cell activity or preventing the migration of immune cells into the CNS, resulting in the prevention of relapses; however, they show limited success in halting MS progression. In this manuscript, we first describe the pathological mechanisms of MS and summarize the approved therapeutics for MS progression. We also review the treatment options for progressive MS (PMS) that are currently under investigation. Finally, we discuss potential targets for novel treatment strategies in PMS.